Gypsies' and Travellers' lived experience of harm: A critical hate studies perspective. (August 2020) - James, Zoë
This article sets out how a critical hate studies perspective can explain and illuminate the hate harms experienced by Gypsies and Travellers in the UK. In doing so, it directly responds to the question of how criminological theory can move beyond existing debates in studies of race and ethnicity and engage more effectively with the wider social sciences. The critical hate studies perspective provides a comprehensive theoretical approach to appreciating the harms of hate in late modernity. This framework challenges existing explanations for bias-motivated violence in society and proposes an approach that acknowledges the overarching role of neoliberal capitalism on individual subjectivity and subsequently the lived experience. By utilising this perspective, it is possible here to discuss the range and depth of hate experienced by Gypsies and Travellers and thus consider its genesis and the potential for positive praxis.